2018
DOI: 10.1016/j.compbiomed.2018.06.031
|View full text |Cite
|
Sign up to set email alerts
|

Migration resistance of esophageal stents: The role of stent design

Abstract: The mechanical advantage of the flared stent was unveiled by the significantly increased contact force, which provided the anchoring effect to resist stent migration. Both the strut diameter and friction coefficient positively correlated with the migration resistance force, and thus the occurrence of stent migration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 40 publications
0
15
0
Order By: Relevance
“…Moreover, the barrel-shaped proximal end of the stent plays a positive role in fixing the stent as well. Several kinds of stent flanges, including flared, dumbbell and barrel shapes, have been used in esophageal stents to prevent stent migration, and the anti-migration force of the stent with a barrel-shaped flange was the largest ( 22 , 23 ). In this cohort of patients, stent migration occurred in 1 patient during follow-up, which was similar to a previous study reported on transcordal stents ( 6 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the barrel-shaped proximal end of the stent plays a positive role in fixing the stent as well. Several kinds of stent flanges, including flared, dumbbell and barrel shapes, have been used in esophageal stents to prevent stent migration, and the anti-migration force of the stent with a barrel-shaped flange was the largest ( 22 , 23 ). In this cohort of patients, stent migration occurred in 1 patient during follow-up, which was similar to a previous study reported on transcordal stents ( 6 ).…”
Section: Discussionmentioning
confidence: 99%
“…Migration behaviors observed in clinical practices [22,23] were not considered in this work. It has been shown that a larger radial/bending strength, correlated with higher contact force between stent and the lesion, could mitigate the migration of a straight stent [24]. The concern of migration was much relieved for both the J-and Y-shaped stents, because each junction configuration, itself, constrained the migration of the stent in a bifurcated lesion [25].…”
Section: Discussionmentioning
confidence: 99%
“…The analysis of the antimigration performance of the stent shows that two standard antimigration methods include structural migration design 2,21,36 and external clinical aids. 37 However, the former leads to complications such as esophageal pain, perforation, and fistula; the latter requires a longer operation time and superior suture technology.…”
Section: Antimigration Functionmentioning
confidence: 99%
“…The other is designing segmental stents to reduce the axial force through structural changes and increase the friction coefficient and contact force of the stent surface. 14,21 The design should balance several mechanical properties of the stents to avoid complications.…”
mentioning
confidence: 99%